Can benthic quality assessment be impaired by uncertain species sensitivities?. Issue 1 (15th March 2017) - Chuševė, Romualda; Daunys, Darius
Abstract: This study tested robustness of mathematically defined species sensitivity with manipulation of disturbance gradient coverage by datasets on two different pressures and two depth zones of the central Baltic Sea. The results indicate large differences of sensitivity values for the same species when depth range changed. After addition of samples from impacted sites to the control datasets, estimated sensitivity values decreased for half of analysed species. Sensitivity of tolerant species appeared to be highly dependent on the coverage of disturbance gradient by the dataset, while sensitive species were highly robust to this effect. Although pressure type and coverage of disturbance gradient by the dataset was important, sensitivity changes were primarily linked to the altered environmental conditions. It is suggested that sensitivity values based on natural variability of pre-selected communities will better integrate the role of important environmental factors and increase robustness of discrimination between disturbed and undisturbed sites. Highlights: Species sensitivities were estimated for different coverage of disturbance gradient by datasets in two depth zones affected by different pressures. Sensitivity values differed significantly between neighboring areas. Sensitivity estimates of tolerant species depend on the coverage of the disturbance gradient by the dataset. Sensitivities based on communities defined by natural conditions are likely to be more robust.